BIM planner : a digital BIM and Lean Construction based prototype to control construction execution (2020)
Digital transformation is taking place in all the industries. In Architecture, Engineering, and Construction (AEC) industry, the guidelines, and philosophies, such as Building Information Modelling (BIM) or Lean Construction (LC), implementation is leading Industry 4.0. Moreover, the combined use of BIM and LC with digital tools increases the potential of its functionalities and result in positive synergies. Thereby, its crucial to design digital APPs that democratize the use of digital tools that simplify and automatize processes. To accomplish this, this study evaluates the design based on user experience or, in other words, design for user experience. To evaluate its usability and usefulness, we use a UX Design evaluation method, called Early design reviews and design walkthroughs. A total of 13 BIM/LC experts, field engineers, construction coordinators, construction managers, chief construction officers, and possible users completed the evaluation. In this study, we found that participants argue that the prototype makes the interaction with 3D models and LC tools friendlier Also, In Colombia would be a practical implementation of this digital tool because most of the companies implement LC, BIM, or digital transformation as a strategic objective. Recommendations and additional tools needed for its correct functioning are provided based on expert's opinions.